CAGFOT - Método de classificação de áreas para a implantação de unidade de geração fotovoltaica, como ação de planejamento da expansão do setor elétrico no MS - Silva, José Humberto Sant Anna da (2022)
This dissertation with the development of an innovative method of classification, assigning scores to areas, to find, among the options analyzed, the most efficient and sustainable. The method was baptized with the name of CAGFOT (Classification of Areas for Photovoltaic Energy Generation). CAGFOT uses indicators, points and weights developed by Sinapse (PROJETO SINAPSE, 2018) and by Caruso Company (CARUSO, 2020), duly adapted for photovoltaic generation, in order to incorporate socio-environmental aspects, which are not considered by the actors responsible for the Electric Generation Expansion Planning, in the decision making of which area to be implemented in the photovoltaic electric energy generation. Therefore, The CAGFOT Method is a tool specialized in a single renewable source of electricity generation, photovoltaics. The CAGFOT Method was applied in the classification of areas available for the generation of photovoltaic electricity, by the Federal Police in Mato Grosso do Sul, which are distributed in the cities of Campo Grande, Dourados, Ponta Porã, Naviraí, Corumbá and Três Lagoas. The application of the CAGFOT Method, in the Federal Police areas in Mato Grosso do Sul, resulted in the area of the Federal Police Station in the City of Três Lagoas/MS as the most efficient and sustainable area, which obtained a score of 9.94 points, two of which 6.79 points for efficiency in the production of electric energy, and 3.15 points for sustainability. The area, despite being one of the smallest available, due to its characteristics and its location, added to the total effective power produced of 1,114.07 Wh.day/m², which corroborates the data from the region of Três Lagoas/MS, which has an irradiation of 5.34 kWh.day/m², the highest irradiation per m² in the state of Mato Grosso do Sul. The CAGFOT Method improves the analysis, as it is presented as another viable and useful tool for analysts who work in the planning of the expansion of electric energy generation, being the first tool to analyze and compare, in an efficient and sustainable way, the options of areas for the use of sunlight.